THE CURRENT STATE OF HEALTH–RESORT TOURISM IN THE SOUTHERN RUSSIA - Tatyana M PORUCHAEVA (Service & Tourism: Current Challenges, 2026)
The article is devoted to the analysis of the current state and prospects for the development of health-resort tourism in the South of Russia in the context of new realities. Many scientific works, by both domestic and foreign scientists, are devoted to the study of the challenges and prospects for the health-resort tourism development. The relevance of the topic is due to the importance of the health-resort tourism for the development of the health care system and the social well-being of the Russian population. In the current geopolitical situation, sanctions pressure, changes in consumer preferences and reorientation of tourist flows to the domestic market, the industry faces many challenges and is experiencing deep structural changes that require careful study and reflection. A comprehensive analysis of various macroeconomic indicators was conducted (a reduction in the number of institutions with a stable bed capacity, a decrease in tourist flow against the backdrop of an increase in the income of health-resort organizations). Based on open statistical data from the Federal State Statistics Service, analytical reports and reviews of consulting companies and various associations, key trends in the health resort industry are considered. The research revealed the multidirectional dynamics of tourist flow indicators and profitability of travel industry organizations (with a reduction in the number of tourists, you can see an increase in income due to higher prices for vouchers, tickets, etc.). The key direction of development can be considered the transition from classic health-resort treatment to the concept of preventive medicine and wellness tourism, accompanied by a change in the consumer profile (rejuvenation of the audience, shorter stay, increased demand for personalized programs).